Breaking the treatment dilemma of Schatzker IV fractures: finite element analysis validates hybrid single-plate with tension screw fixation for synergistic optimization of stability and minimally invasive outcomes - Liu, Mingxiang; Zhou, Zulong; Wu, Chaofan; Wu, Chaoqun; Fang, Run; Zhang, Chengnan; Kong, Lingchao; Ning, Rende (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe core challenge in treating Schatzker type IV tibial plateau fractures lies in balancing mechanical stability with minimally invasive techniques. Traditional double-plate fixation carries a high risk of soft tissue complications, while single-plate fixation provides insufficient mechanical strength. This study aims to systematically evaluate and compare the biomechanical performance of five internal fixation strategies for Schatzker type IV-A and IV-B fractures using finite element analysis (FEA), exploring whether optimized fixation configurations can achieve synergy between minimally invasive treatment and stability.MethodThree-dimensional models of Schatzker type IV-A and IV-B fractures were constructed based on CT data from a 43-year-old male patient. Soft tissue models including ligaments and menisci were established. Five fixation methods were simulated: isolated medial plate (IMLP), medial plate with two posteromedial tension screws (IMLP + 2PMS), medial plate with two lateral tension screws (IMLP + 2LTS), posteromedial and medial double plating (PMP + MLP), and medial and lateral double plating (MLDP). Axial loads from 300 N to 2400 N were applied to simulate conditions ranging from standing to vigorous activity. Implant stress, tibial shaft stress, and fracture fragment micromotion were quantified.ResultUnder a 1200 N load, hybrid fixation modes (IMLP + 2PMS and IMLP + 2LTS) demonstrated superior biomechanical performance. They exhibited the lowest peak implant stress (Type IV-A: IMLP + 2PMS 124.21 MPa; Type IV-B: IMLP + 2PMS 115.64 MPa), significantly better than the IMLP group (∼248 MPa), and comparable or superior to double-plate fixation groups (MLDP, PMP + MLP). While fracture fragment displacement showed no significant differences across all fixation methods, IMLP + 2PMS effectively reduced stress in type IV-B fragments. Regarding stress distribution in the tibial shaft, hybrid fixation provided a more uniform and physiological pattern compared to double-plate fixation. The results indicate differential responses to fixation strategies between type IV-A and IV-B fractures, with type IV-B deriving more pronounced benefits from posteromedial tension screws.ConclusionThe hybrid fixation configuration of a “medial plate combined with tension screws” represents a biomechanically optimal solution for treating Schatzker type IV-A and IV-B fractures. It provides stability comparable to double-plate fixation while significantly reducing implant stress concentration and the “stress-shielding” effect through a minimally invasive approach, achieving a synergy between minimal invasiveness and stability.